Portfolio optimisation with Equally-weighted risk contributions strategy - Kladnik, Tina (2009)
Markowitz has lifted portfolio theory to scientific level by introducing mean-variance framework. Minimum Variance portfolio, unique portfolio on the mean-variance efficient portfolio, has attracted a lot of interest as it is independent of returns expectations. However, the approach has plenty of limitations.